Understanding the factors that shape vaccination ecosystem resilience: a qualitative assessment of international expert experiences and perspectives - Suepattra May; Meaghan Roach; Melissa Maravic; Rachel Mitrovich; Rozanne Wilson; Nadya Prood; Amanda L Eiden (BMJ Public Health)
Introduction ‘Shocks’ or external stressors to vaccination programmes can lead to decreased vaccination coverage rates. The capacity of vaccination ecosystems to effectively respond and adapt to shocks demonstrates programme resilience. This study sought to describe components that contribute to resilience in national immunisation programmes.Methods Mixed-methods study comprising in-depth interviews and surveys with n=30 vaccination programme experts in eight countries (Brazil, Costa Rica, Greece, Japan, Nigeria, Philippines, Spain and the USA). We elicited data on country-specific shocks, associated effects and factors that facilitated or impeded programme resilience. Interviews and open-ended survey responses were analysed qualitatively, with closed-ended survey questions analysed using descriptive statistics.Results Experts described immediate effects of shocks including decreased vaccine uptake and negative perceptions of vaccination from the public and media. Late emerging impacts included increased vaccine hesitancy and vaccine-preventable disease (VPD) rates. Stakeholder education, immunisation information systems (IIS) and programme financing were key factors to strengthening programme resilience. Appropriately trained frontline healthcare personnel can counter vaccine misinformation that otherwise erodes trust and contributes to hesitancy. The COVID-19 pandemic also exposed structural weaknesses in programme resilience, with experts highlighting the need for robust IIS and workforce support to mitigate burnout and strengthen resilience when a shock occurs.Conclusions Our findings provide preliminary insights into factors that experts believe to be associated with vaccination programme resilience. Anticipating, adapting and responding to shocks is central to strengthening systems, ensuring ecosystem resilience and protecting against current and future VPD threats.